Kopačina cave on the island of Brač: new AMS14C dates and their significance for the interpretation of the site’s cultural stratigraphy and excavation methodology (1978–1993) (Archaeologia Adriatica, 2026)
This paper presents two new AMS ¹⁴C dates obtained by dating bone artefacts from Kopačina Cave (island of Brač), which constitute an important contribution to understanding the chronology of this site. The obtained dates are compared with earlier radiocarbon dating results and critically assessed in relation to existing interpretations of the cultural stratigraphy. The results indicate a certain degree of stratigraphic mixing, primarily a consequence of the arbitrary excavation system applied during earlier field campaigns; this highlights the need for caution when using the results of quantitative analyses of lithic and faunal assemblages conducted to date. Within the broader context of the eastern Adriatic Mesolithic, the new dates further call into question the hypothesis of the existence of reliably defined Mesolithic horizons at Kopačina and confirm the importance of revisionary research based on modern methodological standards, including precise stratigraphic documentation and the integrated analysis of different categories of material culture.
Keywords: Kopačina Cave; Brač; Late Upper Palaeolithic; Epigravettian; AMS¹⁴C; stratigraphy; excavation methodology